Repository and CRIS - Mennielli, Michele (2018)
DuraSpace is not for profit organization that provides support and coordination for opentechnologies. We work to ensure that current and future generations have durable and persistent access to our collective digital heritage. Our community is part of an interconnected, worldwide, scholarly ecosystem